Effect of Vegetation Time and Climatic Conditions on trans- Resveratrol Concentrations in Cabernet Sauvignon and Merlot Wines from Different Regions in Turkey - Yaman, Ãœ.R.; Adıgüzel, B.Ç.; Yücel, U.; Çetinkaya, N. (South African Journal of Enology and Viticulture, 2016)
In this study, 21 wine samples obtained from wine manufacturers in Turkey and produced from different grape varieties cultivated in different geographical regions, were analysed to determine their resveratrol concentrations. The HPLC method was used to analyse the trans-resveratrol concentrations of wines. Statistical analysis was done using IBM SPSS Statistics Version 20.0.0. Mean values were compared by using the Tukey test at a confidence level of p = 0.05. The resveratrol concentrations of Cabernet Sauvignon and Merlot grapes were also determined. Since these two varieties are grown widely in many regions of Turkey, they were studied in terms of the relationship of the resveratrol concentrations with parameters such as time of vegetation, total effective temperature, sunshine duration and rainfall. Positive correlations were observed between resveratrol levels and grape varieties, geographical regions and total effective temperature. The results of the statistical analysis showed that resveratrol concentrations also varied depending on vegetation time, sunshine duration and amount of rainfall in the vineyards. This study aimed to identify the relationships between (1) resveratrol concentrations of wines, (2) vegetation time of the grapes and (3) climatic conditions of the respective regions. Moreover, the effects of grape types on resveratrol concentrations were investigated. This study contributes to the body of knowledge by providing results on the utilisation of grapes that have high resveratrol levels for producing wines that have functional properties that are increasingly in demand by consumers.